Transformasi Pengetahuan Lokal Masyarakat Bugis Poleondro dalam Pengolahan Nira Menjadi Gula Merah (Golla Cella) - Hidayat, Rahmat; Nalefo, La; Wianti, Nur Isiyana (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2018)
This study aims to describe the local knowledge of Bugis Poleondro people in processing sap into brown sugar (Golla cella) and to find out the forms of change in local knowledge in processing sap into brown sugar (Golla cella). This research was conducted in Poleondro Village, Poleang Tengah District, Bombana Regency. Determination of informants in this study was done by deliberately choosing based on their knowledge of the processing of brown sugar. The number of informants was four people, two people were adopting brown sugar while maintaining local knowledge and two people who combined local and modern knowledge. The results of this study indicate that local knowledge in processing sap into brown sugar, changes in each stage that is in the stages of processing brown sugar. Changes in knowledge occur from the theological stage to the metaphysical or positive stage, because the results of thinking, market demand, and economic needs are driving changes in knowledge. So it can be concluded that changes in local knowledge occur because some local knowledge is no longer the rationale for processing brown sugar.